Pendampingan Penulisan Artikel Populer bagi Santri Pondok Pesantren Qomaruddin Gresik - Moh Muhtador; Widya Rachel Faradisa; Wahyu Fitrianingrum (Subservire: Jurnal Pengabdian Masyarakat, 2024)
This article discusses the implementation of community service activities with the theme "Assistance in Writing Popular Articles for Students of Qomaruddin Islamic Boarding School, Gresik." The purpose of this activity is to enhance the ability to write popular articles for high school students at Qomaruddin Islamic Boarding School, Gresik, and to provide a basic understanding of writing. The method used is training and socialization conducted in one day on January 26, 2024. The results show a positive response from the community service environment, but long distances become inhibiting factors. Efforts to address this involve solutions such as leaving earlier to overcome this factor. This activity is expected to enhance students' understanding and writing skills and motivate them to continue producing quality work.